Challenges of talent retention and the role of robotic process automation in the covid-19 era: an analysis of organizational strategies and efficiency enhancement - Wadhwa, Swaty; Wadhwa, Kanika (Review of Artificial Intelligence in Education, 2023)
Objective: The objective of this paper is to investigate the challenges of talent retention within organizations during the COVID-19 pandemic, propose effective solutions, and highlight the significance of Robotic Process Automation (RPA) in addressing the issue of Non-Utilized Talent, a key facet of waste within the Lean framework. Method: To achieve this objective, an in-depth analysis of the contemporary organizational landscape was conducted. This analysis included the examination of trends in talent management, the impact of global integration on hiring and development practices, and the role of technology in reshaping human connections. Furthermore, a study of cultural shifts and technological adaptation during the pandemic was undertaken to provide contextual insights. Results: The investigation revealed that as robots increasingly supplant human labor, organizations are compelled to carefully select and nurture their human resources. Amid the COVID-19 pandemic, unique challenges emerged, influencing talent retention strategies. The paper identifies these challenges and presents a range of innovative solutions tailored to the current circumstances. Moreover, the integration of Robotic Process Automation (RPA) was found to play a crucial role in optimizing resource allocation and mitigating Non-Utilized Talent, thereby fostering operational efficiency. Conclusions: In light of the findings, this paper underscores the indispensability of strategic talent retention in the face of evolving work dynamics. The interplay of technology and humanism in the virtual realm emerged as a driving force in fostering genuine connections, both within and outside organizational boundaries. By embracing tailored solutions and harnessing the potential of RPA, organizations can navigate the complex landscape of talent retention and resource optimization. This study contributes to the discourse on contemporary talent management, offering insights that can guide organizations toward resilience, efficiency, and success in an era of profound transformation.